DEVELOPING CALCULATING ABILITY FOR CHILDREN WITH COGGLAK TRADITIONAL GAMES: MENGEMBANGKAN KEMAMPUAN BERHITUNG PADA ANAK DENGAN PERMAINAN TRADISIONAL CONGKLAK - ANDRIKA MUJI LESTARIA; MADE AYU ANGGRENI (incrementapedia, 2020)
This research is motivated by the information that the traditional game congklak is considered to improve the children’s ability to count . The traditional game congklak is one of the learning media that can improve the children’s capability to count. With traditional congklak games it is expected that children can learn to count in a more enjoyable way. The problem formulation in this research is "Does the game tradisoanal congklak affect to the children’s capability to count?”. The purpose of this study is to determine whether the influence of traditional congklak games on the ability to count early childhood in group B in TK Ana Donowati Surabaya.This research uses pre-experimental design with one-group pretest-posttest design. Subjects in this study were 15 children. Data analysis applied in this research is different test technique of pre-test and post-test (t test) from observation of children activity to know the capability of children counting through congklak traditional game activity.The results of data analysis show that 8,16 dan  1,76 with extent α 0,05 and 2,62 at  α 0,01 ,  >  so H0  rejected and H1 (working hypothesis) accepted. It can be concluded that the traditional game congklak has an effect on the ability to count on the group B early childhood TK Ana Donowati Surabaya.